Language Development and Disorders in Spanish-speaking Children - Auza Benavides, Alejandra; Schwartz, Richard G. (Springer International Publishing : Imprint: Springer, 2017)
Prominent researchers from the US, Mexico, Chile, Colombia and Spain contribute experimental reports on language development of children who are acquiring Spanish. The chapters cover a wide range of dimensions in acquisition: comprehension and production; monolingualism and bilingualism; typical development, children who are at risk and children with language disorders, phonology, semantics, and morphosyntax. These studies will inform linguistic theory development in clinical linguistics as well as offer insights on how language works in relation to cognitive functions that are associated with when children understand or use language. The unique data from child language offer perspectives that cannot be drawn from adult language. The first part is dedicated to the acquisition of Spanish as a first or second language by typically-developing children, the second part offers studies on children who are at risk of language delays, and the third part focuses on children with specific language impairment, disorders and syndromes.
Keywords: Linguistics.; Psycholinguistics.; Cognitive grammar.; Developmental psychology.; elektronické knihy; electronic books